(3fXe GdeYdheGJ GdJShjbjI (B/s - (3YQaI, SjO SGdes ((3YeGf(B: s (3GdQGjI ddfTQddfTQ hGdJhRjY(B, s, 2011)
(3eHGOF GdJShjb, egGQGJ GdGJUGd hGdJShjb, eGgjI GdJShjb, EOGQI ehQO GdeYdheGJ, fXGe GdeYdheGJ GdJShjbjI hGdEOGQjI, fMh eYdheGJ JShjbjI MOjKIs
(3HHdjhZQGajG(B: (3U(B.251s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s